Nilai Keadilan Dalam Rekonstruksi Peralihan Hak Atas Tanah - Indriasari, Evy; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2022)
The purpose of the study is to examine conceptually how the transfer of land katas rights and the reconstruction of the transfer of land ha katas are in accordance with the value of justice. The reconstruction of the transfer of land rights refers to article 3d of Government Regulation Number 41 of 1964 concerning the Implementation of Land Division and Compensation Providers which states that it is prohibited to carry out all forms of transferring new rights to agricultural land which results in the landowner concerned owning a plot of land outside the Regency where he resides. However, this provision actually hinders the current transfer of agricultural land rights. This is because one of the parties did not obtain their rights, namely not being able to bind the sale and purchase in the Sale and Purchase Deed and automatically the registration of land to obtain certificates as a proof of their land rights could not be implemented so that the provisions of Article 3d of Government Regulation Number 41 of 1964 concerning the Implementation of Land Division and Compensation Must be immediately revised because they are not in accordance with the value of justice.